2021
DOI: 10.1155/2021/2126967
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mechanism of Action of Herbal Medicine (Gan-Mai-Da-Zao Decoction) for Poststroke Depression Based on Network Pharmacology and Molecular Docking

Abstract: Background. Poststroke depression (PSD) is the most common and serious neuropsychiatric complication occurring after cerebrovascular accidents, seriously endangering human health while also imposing a heavy burden on society. Nevertheless, it is difficult to control disease progression. Gan-Mai-Da-Zao Decoction (GMDZD) is effective for PSD, but its mechanism of action in PSD is unknown. In this study, we explored the mechanism of action of GMDZD in PSD treatment using network pharmacology and molecular docking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The underlying pathophysiology of depression is associated with the damage of monoamine transmission systems ( LeMoult and Gotlib, 2019 ). In fact, clinical studies have found that Chaihu Jia Longgu Muli Decoction , Gan Mai Da Zao Decoction , Xiao Yao San has a good antidepressant effect by preventing dopaminergic transmission in rats ( Ding et al, 2021 ; Wan et al, 2021 ; Wang YT. et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying pathophysiology of depression is associated with the damage of monoamine transmission systems ( LeMoult and Gotlib, 2019 ). In fact, clinical studies have found that Chaihu Jia Longgu Muli Decoction , Gan Mai Da Zao Decoction , Xiao Yao San has a good antidepressant effect by preventing dopaminergic transmission in rats ( Ding et al, 2021 ; Wan et al, 2021 ; Wang YT. et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…This core active ingredients of Chaihu Jia Longgu Muli Decoction consists of Chaihu (Bupleurum) , Muli (Ostrea gigas) , which are pivotal in treating depression ( Wang Y. et al, 2023 ). The key active compounds in the Gan Mai Da Zao Decoction were identified as Quercetin , Luteolin , Kaempfero l, Naringenin , and Isorhamnetin , contributing significantly to its antidepressant effect ( Ding et al, 2021 ). Quercetin , Apigeni and Luteolin , key components of the Xiao Yao San , effectively mitigate the progression of depression ( Chen, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis of AR/YPFS-related genes was performed to identify genes in the biological processes (BP), cellular components (CC), molecular functions (MF) categories, and pathways using the ClusterProfiler R Package ( Wang et al, 2022 ). The data obtained were visualized by using bioinformatics 8 ( Ding et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, network pharmacology has been gradually applied in the field of TCM, which reveals the mechanism of drugs action based on the Chinese herbal medicine-components-targets-pathways-disease network [ 12 ]. This coincides with the characteristics of multi-components, multi-targets, and multi-pathways of TCM.…”
Section: Introductionmentioning
confidence: 99%